Cholesterol Level in Covid-19 Patients Related to Severity and Mortality: A Case Series and Literature Review - Anggarda Kristianti Utomo; Haryati Haryati (Indonesian Society of Respirology (ISR), 2021)
Coronavirus Disease 2019 (COVID-19) is a communicable disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). December 2019 in Wuhan, China, is the time and place where the first pneumonia case which SARS-CoV-2 causes was found, and WHO designated COVID-19 as a pandemic by March 2020. There are reported cases of dyslipidemia associated with SARS patients, albeit rare. Several case reports showed lower cholesterol levels compared to healthy subjects. Therefore, some argued that dyslipidemia could occur in COVID-19. Several studies have revealed that hypolipidemia is positively correlated with the severity of COVID-19. In Ulin Regional Hospital Banjarmasin, several cases found higher cholesterol levels in asymptomatic and mild-moderate COVID—19 survivor compared to patients with severe/critical COVID-19and non-survivor. Two patients in the non-survivor group showed a significant decrease in cholesterol level compared to baseline, and five patients had <150 mg/dL cholesterol level during the examination. Four mild-moderate COVID-19 survivors had cholesterol levels that were greater than 150 mg/dL at the first examination and did not decrease during the evaluation. Cholesterol is thought to play an important role in the pathological development of COVID-19, and it is associated with severity and mortality, which requires further studies.